Announcement of Retraction - Damaro Olusoji Arubayi (Universitas Mercu Buana, 2023)
Retraction to:Article Title: Coercive Management Behavior and Employees’ Satisfaction in TheHospitality Sector (A Study of Selected Hotels in Warri Delta State)Authors: Damaro Olusoji Arubayi This article has been retracted by the publisher based on the following reason This is based on the author's recognition to the editor that the author admits that he forgot to have submitted the same article to another journal.